Osteopetrosis-like disease in a cat with respiratory distress - Fujita, M.(Nippon Veterinary and Life Science Univ., Musashino, Tokyo (Japan)); Takaishi, Y; Nagae, H; Watanabe, N; Hasegawa, D; Taniguchi, A; Orima, H (Journal of Veterinary Medical Science, 2007)
Magnetic resonance (MR) and computed tomography (CT) were performed in an 8-year-old, spayed female cat with chronic effort respiration at the inspiration phase and stertor. Increased bone opacity in the areas of the head, neck and thorax were observed on radiography. MR images showed no signal intensity on both transverse T1WI and T2WI of the nasal cavity. CT revealed increased bone density and hypertrophy of the nasal turbinate and a narrowed nasal passage. From these results, we concluded this case had osteopetrosis-like disease, and that the respiratory distress was caused by hypertrophy of the nasal turbinate.